2006
DOI: 10.1371/journal.pmed.0030260
|View full text |Cite|
|
Sign up to set email alerts
|

Eight Americas: Investigating Mortality Disparities across Races, Counties, and Race-Counties in the United States

Abstract: BackgroundThe gap between the highest and lowest life expectancies for race-county combinations in the United States is over 35 y. We divided the race-county combinations of the US population into eight distinct groups, referred to as the “eight Americas,” to explore the causes of the disparities that can inform specific public health intervention policies and programs.Methods and FindingsThe eight Americas were defined based on race, location of the county of residence, population density, race-specific count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
524
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 626 publications
(557 citation statements)
references
References 31 publications
21
524
0
3
Order By: Relevance
“…16 For example, in the Eight Americas Study, the authors identified 7 distinct groups within the United States based on race, geographic location, and income and found significant differences in life expectancy. 34 These groups are, in order of decreasing life expectancy, Asian Americans (84.9 years), whites living in rural Northern Plains/Dakotas, low-income whites in Appalachia and the Mississippi Valley, western Native Americans, middle-income blacks, southern rural blacks, and blacks in poor urban areas (71.1 years), representing a 14-year difference between the highest and lowest group. CVD was the greatest source of differences in life expectancy.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…16 For example, in the Eight Americas Study, the authors identified 7 distinct groups within the United States based on race, geographic location, and income and found significant differences in life expectancy. 34 These groups are, in order of decreasing life expectancy, Asian Americans (84.9 years), whites living in rural Northern Plains/Dakotas, low-income whites in Appalachia and the Mississippi Valley, western Native Americans, middle-income blacks, southern rural blacks, and blacks in poor urban areas (71.1 years), representing a 14-year difference between the highest and lowest group. CVD was the greatest source of differences in life expectancy.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
“…First, socioeconomically disadvantaged populations suffer from a great burden of Framingham risk factors. 34,[268][269][270][271][272][273][274] This is an important consideration because it may be possible to use clinical 109 and public health interventions 92 to reduce this burden, thereby narrowing health disparities. Second, social and economic stresses lead to a biological wear and tear, or allostatic stress response, [275][276][277][278][279][280] involving a number of pathways, including stimulation of stress hormones, [280][281][282] inflammation, 283 endothelial dysfunction, thrombosis, vascular hyperreactivity, 270,274,[284][285][286][287] and metabolic disturbances.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…An area classification allows a move away from one-dimensional approaches to a multidimensional understanding of the health of areas through summarising the main patterns across a range of variables. Knowing and understanding how causes of death vary and coassociate within an area is important for the effective targeting of policies, resources and location of services (Murray et al 2006). This paper details the construction of an area classification of mortality patterns in England andWales (2006-2009).…”
Section: Introductionmentioning
confidence: 99%
“…9,26,27 In the EHDIC-SWB sample, African-American and whites had similar access to health care resources which has been shown to produce similar health outcomes. 17,28 Furthermore, Thorpe and colleagues demonstrated that African-American men in EHDIC-SWB engaged in preventive health screenings more than white men.…”
Section: Discussionmentioning
confidence: 99%